System-Object Determinant Analysis. Construction of Genetic and Partitive Classifications of the Subject Area - Matorin, S. I.; Mikhelev, V. V. (Scientific and technical information processing, 2023)
This paper considers the second and third stages of a system-object determinant analysis, including the construction of the genetic and partitive classifications of the subject area. Class and phenomenon systems are described using the single system-object approach Node–Function–Object and formalization means in the language of descriptive logic ALCHOIQ (D). Partitive classification is obtained using a formal-semantic normative system based on the classification of alphabetical nodes and links. Examples of constructed genetic and partitive classifications are given.